Distribution, Genetic Diversity and Population Structure of Aegilops tauschii Coss. in Major Wheat-Growing Regions in China - Haiyan Yu (Agriculture, 2021)
Aegilops tauschii Coss. is known as a noxious grass weed seriously affecting wheat quality and yield. To investigate its present occurrence in wheat fields and the potential genetic diversity of the grass weed in China, a filed survey covering major wheat production regions was conducted during 2017–2019. Seeds of different Ae. tauschii populations collected from the survey were analyzed with Simple Sequence Repeats (SSRs) technique. Results showed that Ae. tauschii was occurring in each of the provinces surveyed with varied occurrence frequency ranging from 0.91% in Sichuan Province to 92.85% in Henan Provinces. Eighty alleles with size ranging from 98 bp to 277 bp were detected from the 192 collected Ae. tauschii populations with 17 SSR markers. Ae. tauschii, in this study, exhibited a moderately high level of genetic diversity, high differentiation, deficient heterozygosity and limited gene flow. Compared with other provinces, Hubei populations possessed relatively low genetic diversity. Dendrogram analysis showed that genetic distance did not seem to be related to geographic distribution. Additionally, STRUCTURE analysis suggested that Ae. tauschii populations in wheat fields of China can be divided into three groups, which was further supported by cluster analysis. Among the three groups, solely 7% of the total variation was detected, whereas the majority variation (67%) occurred among different populations within same group. Undoubtedly, such information will help us to better understand population relationships and spread of Ae. tauschii in China and will provide a new perspective for its integrated management.